Unmasking of Gitelman Syndrome during Pregnancy in an Adolescent with Thyrotoxic Crisis - Ratna Acharya; Kiran Upadhyay (MDPI AG, 2021)
Background. Gitelman syndrome (GS) is an inherited salt-losing renal tubulopathy characterized by hypokalemic metabolic alkalosis with hypomagnesemia and hypocalciuria. Patients can be asymptomatic until late adolescence or adulthood, and hence may be discovered incidentally during presentation with other illnesses. GS has been described in association with thyroid disorders and should be considered in patients with hyperthyroidism and persistent hypokalemia, especially in those with associated hypomagnesemia and hypocalciuria. Case summary. In this report, we describe an 18-year-old female who presented with hyperemesis gravidarum and thyrotoxicosis, and was incidentally found to have GS, confirmed by the sequence analysis of SLC12A3. Conclusions. Thyroid dysfunctions, such as hypothyroidism, thyrotoxicosis, and thyroid nodules, may develop during pregnancy. A structural homology between the beta-human chorionic gonadotropin and thyroid stimulating hormone molecules, as well as their receptors is probably the basis for the transient thyrotoxicosis crisis during pregnancy. Since hyperemesis in pregnancy can also lead to hypokalemia and alkalosis, a high index of suspicion for GS during pregnancy is required for timely diagnosis and management.